Solving probability reasoning based on DNA strand displacement and probability modules. (December 2017) - Zhang, Qiang; Wang, Xiaobiao; Wang, Xiaojun; Zhou, Changjun
Abstract: In computation biology, DNA strand displacement technology is used to simulate the computation process and has shown strong computing ability. Most researchers use it to solve logic problems, but it is only rarely used in probabilistic reasoning. To process probabilistic reasoning, a conditional probability derivation model and total probability model based on DNA strand displacement were established in this paper. The models were assessed through the game "read your mind." It has been shown to enable the application of probabilistic reasoning in genetic diagnosis.